From Territoriality to Functional Control: A Jurisdictional Test for Cross-Border Cyberterrorism Operations - Nadiah Khaeriah Kadir (Punggawa Law Review, 2026)
Cyberterrorism repeatedly challenged jurisdictional reasoning because its conduct, infrastructure, effects, and evidence were distributed across multiple states, making territorial and effects-based claims both over-inclusive and operationally fragile. This article examined why classical jurisdiction bases produced recurring gaps and conflicts in cross-border cyberterrorism prosecutions and proposed a control-oriented solution. It developed a Functional Control Test that assessed jurisdictional priority by reference to operational direction, meaningful leverage over enabling infrastructure, deliberate targeting and foreseeable coercive effects, and the lawful feasibility of securing decisive electronic evidence. The analysis showed that the test reduced inflated claims driven by incidental routing or compromised nodes, while still accommodating legitimate concurrent jurisdiction for deliberately targeted victim states. It also clarified that strong jurisdiction to prescribe and adjudicate did not entail unilateral cross-border enforcement, preserving consistency with sovereignty and non-intervention constraints. The study concluded that functional control provided a more reviewable and practicable nexus standard for allocating prosecutorial leadership and structuring cooperation in cyberterrorism cases.